Electric Vehicle Battery Condition Monitoring System - Prof. Preeti S B; Shirakol, Prof. Shrikanth; Chinmayi Timalapur; Darshan H Chabbi; Divya M Agadi; Sudeeksha S S (International Journal of Engineering and Management Research, 2024)
Most vital and expensive components of electric vehicles is the battery. Of course, the battery is the only source of electricity for an electric vehicle. However, the vehicle's power supply eventually declines, resulting in decreased performance. For battery manufacturers, this is a major concern. In this paper, it is proposed to use IoT approaches to monitor and display the battery performance. Here, the various battery metrics, including voltage, current, and temperature, are tracked, observed, and shown. This alerts the user to prevent the battery from being overcharged or deeply discharged. With the application of various sensors, observation can be carried out. Data on voltage, current, and temperature are sent to a microcontroller unit, which subsequently transmits battery data via the cloud for display. Real-time data of voltage, current, and temperature may be displayed by the monitoring system, and the data can be seen on an Android smartphone and a computer at the same time. As a result, we might be able to increase the battery's efficiency and lifespan. The user interface and results presentation are the two main components of the proposed IoT-based battery monitoring system. According to test results, the system is able to recognize weakened performance of the battery and notifies the user for further use.